Karakteristik Ekonomi dan Akumulasi Investasi Rumah Tangga di Indonesia - M Faisal Akbar (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2020)
Abstract This study aims to analyze household characteristics and investment behavior. There are indications that household characteristics are alleged to have an influence on their investment behavior. The study uses IFLS data sources and data analysis techniques using the Fixed effect method. The results show that investment patterns have been significantly influenced by several characteristics including: income, age of the head of the family and residence. This study also traced non-linear relationships with the characteristics of the age of the head of the family. The study found that middle-income households have a higher accumulation of assets compared to productive assets accumulation in high-income households and low-income households